Safety and efficacy of combination nivolumab plus ipilimumab in patients with advanced melanoma: results from a North American expanded access program (CheckMate 218). Issue 1 (23rd November 2020) - Hodi, F. Stephen; Chapman, Paul B.; Sznol, Mario; Lao, Christopher D.; Gonzalez, Rene; Smylie, Michael; Daniels, Gregory A.; Thompson, John A.; Kudchadkar, Ragini; Sharfman, William; Atkins, Michael; Spigel, David R.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : CheckMate 218, a North American expanded access program (EAP), investigated nivolumab plus ipilimumab in patients with advanced melanoma. Safety and efficacy, including 2-year survival in clinically relevant patient subgroups, are reported. Eligible patients were aged ≥18 years with unresectable stage III/IV melanoma, an Eastern Cooperative Oncology Group performance status of 0/1, and no prior checkpoint inhibitors. Patients received nivolumab 1 mg/kg plus ipilimumab 3 mg/kg every 3 weeks for 4 cycles (induction) followed by nivolumab 3 mg/kg every 2 weeks (maintenance) until progression or unacceptable toxicity or a maximum of 48 weeks. Safety and overall survival (OS) data were collected. This EAP included 754 treated patients from the USA ( n = 580) and Canada ( n = 174). Median follow-up time was 17.8 months. All-grade and grade 3–4 treatment-related adverse events were reported in 96% and 53% of patients and led to treatment discontinuation in 36% and 26% of patients, respectively. OS rates at 12 and 24 months were 82% [95% confidence interval (CI) 79–84] and 70% (95% CI 66–74), respectively. Twenty-four-month OS rates were 63% in patients aged ≥75 years, 56% in patients with elevated lactate dehydrogenase levels, 73% in patients with BRAF wild-type tumors, 70% in patients with BRAF mutant tumors, and 56% in patients with mucosal melanoma. In this EAP, nivolumab plus ipilimumab demonstrated high survival rates and safety outcomes consistent with those from randomized clinical trials, further supporting the use of this combination for advanced melanoma across multiple subgroups.